Biogenic terbium oxide nanoparticles as the vanguard against osteosarcoma - Iram, Sana; Khan, Salman; Ansary, Abu Ayoobul; Arshad, Mohd; Siddiqui, Sahabjada; Ahmad, Ejaz; Khan, Rizwan H.; Khan, Mohd Sajid (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2016)
The synthesis of inner transition metal nanoparticles via an ecofriendly route is quite difficult. This study, for the first time, reports synthesis of terbium oxide nanoparticles using fungus, Fusarium oxysporum. The biocompatible terbium oxide nanoparticles (Tb2O3 NPs) were synthesized by incubating Tb4O7 with the biomass of fungus F. oxysporum. Multiple physical characterization techniques, such as UV-visible and photoluminescence spectroscopy, TEM, SAED, and zeta-potential were used to confirm the synthesis, purity, optical and surface characteristics, crystallinity, size, shape, distribution, and stability of the nanoemulsion of Tb2O3 NPs. The Tb2O3 NPs were found to inhibit the propagation of MG-63 and Saos-2 cell-lines (IC50 value of 0.102 mu g/mL) and remained non-toxic up to a concentration of 0373 gg/mL toward primary osteoblasts. Cell viability decreased in a concentration-dependent manner upon exposure to 10 nmTb(2)O(3) NPs in the concentration range 0.023-0373 mu g/mL Cell toxicity was evaluated by observing changes in cell morphology, cell viability, oxidative stress parameters, and FACS analysis. Morphological examinations of cells revealed cell shrinkage, nuclear condensation, and formation of apoptotic bodies. The level of ROS within the cells an indicator of oxidative stress was significantly increased. The induction of apoptosis at concentrations <= IC50 was corroborated by 4',6-diamidino-2-phenylindole dihydrochloride (DAPI) staining (DNA damage and nuclear fragmentation). Flow-cytometric studies indicated that the response was dose dependent with a threshold effect. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Cytotoxicity; fusarium oxysporum; Osteosarcoma; Tb2O3 nanoparticles

Biomimetic synthesis of CdSe nanoparticles with potential bioimaging applications - Ansary, Abu Ayoobul; Uddin, Imran; Khan, Muhammed I. (International Journal of Pharmaceutical Sciences and Research, 2017)
This study presents in vitro biomimetic synthesis of CdSe nanoparticles using the enzyme, NADPH dependent-Nitrate reductase purified from fungus, Fusarium oxysporum. The synthesis of CdSe nanoparticles was accomplished in the presence of a synthetic peptide having amino acid sequence (γ-Glu-Cys-Glu-Cys)-Gly, which acted as binding molecule. The nanoparticles were synthesized in the size range of 3.9–9.0 nm was analysed using TEM. Further characterization of nanoparticles was done using techniques such as UV, PL, XPS, and FTIR. The as-synthesized CdSe nanoparticles were water dispersible containing free reactive amino groups. These CdSe nanoparticles were conjugated with bi-antennary and tri-antennary glycopeptides opening up the possibilities for their applications in bioimaging. These significant observations will help better understand the mechanism of biosynthesis of fluorescent nanoparticles using fungi. These findings promise an alternative strategy for an eco-friendly, economical, and large-scale synthesis of water dispersible CdSe nanoparticles. These CdSe nanoparticles have promising biomedical-imaging applications without a need for further functionalization.